Influence of Dielectric Media on the Plasma Characteristics in DBD Discharge - Khaleel, Sarah Faris; Abbas, Qusay A. (Iraqi Journal of Science, 2022)
The study of the surface plasma characteristics under atmospheric pressure is a new branch and tool in physics. Building generation dielectric barrier discharge (DBD) system at atmospheric pressure and studying its thermal characterizations. The discharge was produced by applying a high voltage of 20 kV with a frequency of 8 kHz. The thermal characterization was done by measuring discharge temperature for different horizontal surface areas and different types of insulating material. The results indicated that the effect of the area and the type of insulator affect the discharge (increasing or decreasing) according to the operation conditions because they affect, as expected, the DBD . The plasma temperature increased with the decrease of the surface area, which resulted in the increase of the discharge voltage across the gap; accordingly, the discharge across the gap grew.